Improved Sleep in Military Personnel is Associated with Changes in the Expression of Inflammatory Genes and Improvement in Depression Symptoms - Livingston, Whitney S.; Rusch, Heather L.; Nersesian, Paula V.; Baxter, Tristin; Mysliwiec, Vincent; Gill, Jessica M. (Frontiers in Psychiatry, 2015)
Study Objectives: Sleep disturbances are common in military personnel and are associated with increased risk for psychiatric morbidity, including posttraumatic stress disorder and depression, as well as inflammation. Improved sleep quality is linked to reductions in inflammatory bio-markers; however, the underlying mechanisms remain elusive. Methods: In this study we examine whole genome expression changes related to improved sleep in 68 military personnel diagnosed with insomnia. Subjects were classified into the following groups and then compared: improved sleep (n=46), or non-improved sleep (n=22) following three months of standard of care treatment for insomnia. Within subject differential expression was determined from microarray data using the Partek Genomics Suite analysis program and the interactive pathway analysis was used to determine key regulators of observed expression changes. Changes in symptoms of depression and posttraumatic stress disorder were also compared. Results: At baseline both groups were similar in demographics, clinical characteristics, and gene-expression profiles. The microarray data revealed that 217 coding genes were differentially expressed at the follow-up-period compared to baseline in the participants with improved sleep. Expression of inflammatory cytokines were reduced including IL-1β, IL-6, IL-8 and IL-13, with fold changes ranging from -3.19 to -2.1, and there were increases in the expression of inflammatory regulatory genes including toll-like receptors 1, 4, 7, and 8 in the improved sleep group. Interactive pathway analysis revealed 6 gene networks, including ubiquitin which was a major regulator in these gene-expression changes. The improved sleep group also had a significant reduction in the severity of depressive symptoms. Conclusions: Interventions that restore sleep likely reduce the expression of inflammatory genes, which relate to ubiquitin genes and relate to reductions in depressive symptoms.